Too cosy for comfort? : a media ethical investigation into the Presidential Press Corps - Van Zyl, Elizabeth Margaretha; Van Zyl, Lizma (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2003.